EXPLORING THE LANGUAGE USE IN WHATSAPP AS STUDY PRAGMATICS - Ajeng Puji Lestari (Fakultas Komunikasi, Sastra, dan Bahasa, 2019)
The present study investigated the structural classification analysis of conversation andpreference structure in WhatsApp emoticon usage. Yule (1996) illustrated that there aretypes of structural classification in the first part of conversation such as proposal, offering,requesting, and giving assessment. On the other hand, the second part of conversation wasthe response utterances either preffered or dispreffered that were also occurred inadjacency pair in several expressions such as questioning sequence, insertion sequence,thanking expression, and parting expression. The present study applied a quantitativemethod to obtain data by distributing a set of questionnaires to 36 users of WhatsApp. Theresults showed that variables suggested by Yule (1996) were found in 11 data resources ofchatting which were also accompanied by the use of WhatsApp emoticon. Thus, it is arguedthat WhatsApp emoticons are becoming the important tools as an online facilitator forcommunication because emoticons can enhance the messages and can help to expressemotions or feelings.